VD_FINDINFO Jug / 2011 / 307 vom 21. Dezember 2011 - VD Tribunal cantonal (2011)
OEUVRE D'ART, OEUVREDROIT D'AUTEUR, CONCURRENCE DÉLOYALE, DOMMAGES-INTÉRÊTS | 41 CO, 107 CPC, 5 let. c LCD, 2 al. 1 LDA, 2 al. 2 LDA, 9 LDA